Prokrastinasi Belajar Mahasantri di Lingkungan Kampus Institut Dirosat Islamiyah Al-Amien Prenduan - Idul Fitri; Heri Fadli Wahyudi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This research aims to give an overview and reveal the causes of learning procrastination experienced by the students of the intensive program of the Institute of Dirosat Islamiyah Al-Amien Prenduan. This research is a type of descriptive research with qualitative approach with data retrieval techniques in the form of observations, interviews, documentation, research subjects used in this research, is 15 people in the intensive program. The results showed that the procrastination occurred in the form of delays to the work of academic tasks with a diversion to activities that are entertainment, while the cause of procrastination of learning in students, The Institute of Dirosat Islamiyah Al-Amien Prenduan. Among others are: 1) Lazy and bored; 2) Poor processing and time control; 3) Difficulty in concentrating; 4) Difficulty finding references; 5) Not understanding lessons and assignments; 6) Number of activities and lack of facilities; 7) Not understanding the nature of learning.